Pengaruh Green product, Green Price dan Green Brand Image Terhadap Keputusan Pembelian Produk Galon Le Minerale - Ulya, Salma Novita; Aqmala, Diana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study was to analyze the effect of Green product, Green Price, and Green Brand Image on the Purchase Decision of Le Minerale Gallons. The data used in this study used a Google Form-based questionnaire, and the valid data collected were 120 respondents. The sampling method in this study was purposive sampling. The testing tool used is SPSS. The analysis method in this study uses quantitative primary data, using multiple linear analysis research methods, the test stages carried out are: validity, reliability, multiple linear regression, F test, t test and coefficient of determination. The results of this study indicate that the variables Green product, Green Price, Green Brand Image partially and simultaneously have a positive and significant effect on purchasing decisions. This research provides significant benefits for Le Minerale gallon companies by opening up in-depth insights into consumer preferences for sustainability aspects, such as green product, green price and Green Brand Image. The results of this study can guide more targeted marketing strategies, allowing companies to increase product appeal, expand market share, and build stronger relationships with environmentally conscious consumers. By deeply understanding consumer purchasing decisions, companies can optimize their sustainability efforts to achieve greater positive impact in the market.